THE INFLUENCE OF FINANCIAL DISTRESS, CHANGE OF MANAGEMENT, COMPANY GROWTH, CAP SIZE AND AUDIT OPINION ON VOLUNTARY SWITCHING AUDITORS IN MANUFACTURING COMPANIES (Jurnal Ipteks Terapan, 2023)
The aim of this research is to examine the effect of financial distress on Management Change, growth company, Size  HOOD,  And  opinion  audit of voluntary auditor switching changes in manufacturing companies listed on the Indonesian Stock Exchange (BEI) for the 2019-2022 period. Secondary data comes from financial reports Which published by market capital in Indonesia stock exchange. The type of research used in this research is testing hypotheses, using a purposive sampling method. There are 44 data samples used as research objects. This research uses regression analysis logistics for testing hypotheses. The research results show that financial distress, management changes, company growth, KAP size, have no effect on Voluntary Auditor Switching while Audit Opinion has an effect on Auditor Switching Voluntary. It is known from the SPSS test that the value is 0.000